Pemanfaatan OpenSID sebagai Media Sistem Informasi Desa Cemara Jaya Halmahera Timur - Gamaria Mandar; Abdul Haris Muhammad; Bayu Ajisaputro; M.Ikbal Hidayullah (Universitas Pahlawan Tuanku Tambusai, 2022)
Service to the community by utilizing technology is an obligation that must be carried out by every village government, including the Cemara Jaya village government in Wasile, East Halmahera, public services using manual methods can cause several problems such as loss of documents and undocumented letters issued by Cemara Jaya village government in a structured manner. This service is carried out in an effort to assist the village government and its community in using the Cemara Jaya Village Information System (SID). The training and mentoring methods that have been carried out show that the service system carried out by the Cemara Jaya Village government is more efficient, saves time and data management that was previously manual-based to digital-based in the form of a village information system.